2016
DOI: 10.15804/tner.2016.45.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Science Teacher Communication Behavior in Jordan

Abstract: Th e purpose of this study was to determine student perceptions of science teacher communication behavior in the classroom environment in Jordan. A total of 1,093 participants in the study completed the Teacher Communication Behavior Questionnaire (TCBQ). Results indicated the overall mean of teacher communication behavior to be 3.9 and showed statistically signifi cant diff erences in gender perceptions on all fi ve scales of the TCBQ. Results also showed statistically signifi cant diff erences in student per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies have also found that mathematics teachers viewed mathematics as a male domain and tended to attribute the success of boys to ability while attributing the success of girls to effort (Sarouphim and Chartouny, 2017). This result is supported by another study conducted in Jordan, where it was found that boys perceive receiving more encouragement from their science teachers than the girls did (Mahasneh et al, 2016).…”
Section: The Environmentmentioning
confidence: 79%
“…Studies have also found that mathematics teachers viewed mathematics as a male domain and tended to attribute the success of boys to ability while attributing the success of girls to effort (Sarouphim and Chartouny, 2017). This result is supported by another study conducted in Jordan, where it was found that boys perceive receiving more encouragement from their science teachers than the girls did (Mahasneh et al, 2016).…”
Section: The Environmentmentioning
confidence: 79%
“…On the other hand, Walsh (2006b, p. 3) focuses on special communication patterns found in language classrooms and features of classroom discourse, such as elicitation techniques or repair strategies. As discussed by Mahasneh, Musslim and Shammout (2016), learner-teacher interactions can also be viewed from the broader perspective of classroom learning environments and systems theory, according to which the behaviours of diff erent participants in a social situation both determine and are determined by each other. For the purposes of this paper, we understand classroom communication broadly as 'a form of institutional communication' which has its special characteristics and involves both teacher-learner and learner-learner interaction.…”
Section: Silva Bratož Mojca žEfranmentioning
confidence: 99%